Investigating the information technology courses for pre-service and in-service english teachers in hong kong (2011)
This paper focuses on the views of twenty-six pre-service and eight in-service English teachers in Hong Kong concerning the information technology courses in their teacher education programmes. The findings of the study show that while both software applications and technological integration in teaching are highlighted in the course outline, the instructor focused more on the application aspect, with the technology integration being less emphasised. Another important finding is that PowerPoint was still the most commonly used application in teaching. Likewise, usually the involved pre-service and in-service teachers just simply used different computer applications as alternatives to traditional teaching resources. This may reflect the fact that the information technology courses are not adequate to prepare teachers to teach with it.Este artículo se centra en las opiniones que tienen veintiséis profesores practicantes y ocho profesores de inglés en Hong Kong sobre los cursos de información de tecnología en sus programas de licenciatura. Los resultados muestran que mientras las aplicaciones de  software y la integración de tecnología se destacan en el esquema del curso, el instructor se enfoca más en los aspectos de aplicación. A su vez, la integración de tecnología no tuvo tanto énfasis. Otro hallazgo importante es que Power Point siguió siendo la aplicación más empleada en la enseñanza. Asimismo, los docentes y profesores practicantes involucrados generalmente solo usan diferentes aplicaciones de computadores como alternativas a los recursos de enseñanza tradicional. Esto puede reflejar el hecho de que los cursos de información de tecnología no son adecuados para preparar a los profesores para hacer uso de esta en su labor educativa.